Experimental investigation of concrete edge failure for single stud anchors and anchor groups after fire exposure. (10th January 2021) - Tian, Kaipei; Ožbolt, Joško; Hofmann, Jan
Highlights: Concrete edge failure load of anchors decreases significantly with increase of fire exposure. After fire the failure mode shows to be a combination of concrete edge failure and pryout failure. The shear stiffnesses of the studied anchors are reduced significantly after fire exposure. The group effects of anchors for the concrete edge failure after fire exposure are investigated. Abstract: In the present study headed stud anchors with single stud, two- and four-stud anchor groups are exposed to various duration of fire and after cooling (cold state) loaded in shear perpendicular to and towards the free edge of concrete member up to failure. The standard ISO 834 fire curve with fire durations of 15 min and 60 min are employed in the experiment. The influence of the number of studs and the duration of fire on the load-bearing behaviour of anchors is experimentally investigated. As expected, the results show that the anchor behaviour is significantly influenced by the fire exposure. Due to the thermally induced damage of concrete the failure pattern is changing from the typical concrete edge failure to a combination of concrete edge failure and pryout failure. For fire duration of only 15 min, the reduction of resistance can be more than 50% of the reference resistance. After 60 min of fire, the reduction factor is approximately corresponding to the reduction factor for 90 min of fire exposure according to current Eurocode 2. Considering concrete capacity method (CC-method), it is demonstrated that simply replacing the compressive strength of concrete at ambient temperature with the reduced compressive strength after fire is not appropriate for predicting the resistance of single stud anchors and anchor groups. However, the projected area ratio of the fracture seems to be valid for predicting the resistance of anchor group based on the reduced resistance of corresponding single stud anchor after fire exposure.